Impact of Toll Road Development on Modern Retail Growth In Indonesia - Putra, Arditya Prakoso (Journal Research of Social Science, Economics, and Management, 2023)
This study would like to see the impact of toll road development toward retail industry growth especially modern retail by taking the construction of the Trans Java toll road in Indonesia. Using a difference-in-differences (DID) approach, this study analyzes the effect of Trans Java Toll Road in 7.656 villages crossed by toll road from 2006 to 2018. The result shows that, on average, after Trans Java toll road program, the trend of increasing the number of minimarkets in villages crossed by the Trans Java toll road is 0.53 units larger compared to The villages that doesn't crossed by Trans Java toll road. But the results show that there is no significant effect of the Trans Java toll road on the number of traditional stores, namely the grocery store as traditional retail. It can be seen that toll road development programs tend to open up access to the growth of the modern retail industry in Indonesia.